KUALITAS PELAYANAN BIDANG PENDIDIKAN DASAR DI KECAMATAN KULISUSU KABUPATEN BUTON UTARA - La Mudae; Jopang Jopang; Nana Mulyana (Journal Publicuho, 2021)
The purpose of this study was to determine and analyze the quality of services in the field of basic education in Kulisusu District, North Buton Regency. This study uses a descriptive qualitative approach. There were 11 research informants consisting of the Head of the Education and Culture Office, Head of the GTK Division of the Education and Culture Office, Head of SD Lamoahi, Head of SD Lelamo, Head of SDN Wa Ode Buri, 3 teaching staff and 3 Committee Chairs. The selection of informants was done purposively. Data were collected through observation, interviews and document studies. The data collected was then analyzed descriptively qualitatively.The results showed that the quality of service in the field of basic education in Kulisusu District, North Buton Regency was not optimal. This can be seen from the 10 dimensions measured, indicating that the indicators of tangible, credibility, competent, reliable and security are not yet optimal and still require serious improvement. Meanwhile, indicators of access, courtersy, competent, responsiveness, communication, and understanding of the customer have been well fulfilled